Penanaman Pola Asuh dan Keteladanan Orang Tua terhadap Pembentukan Nilai Anti Korupsi Anak di Keluarga - Nursalim Nursalim; Wikan Sasmita; Hamida Ulfa Fauziah; Etty Andyastuti; Agus Widodo; Suratman Suratman (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
: This study aims to analyze the role of family in instilling anti-corruption values in children through habituation and exemplary practices within the household environment. The family is considered the primary and most strategic institution in shaping children’s character, particularly in preventing corruptive behavior from an early age. This research employed a qualitative descriptive approach, focusing on observation, interviews, and documentation with parents as the main subjects. The findings reveal that honesty (78%) and responsibility (70%) are the most emphasized values, followed by discipline (65%), while simplicity (52%) tends to receive less attention. The results indicate that consistent parental supervision, the establishment of daily routines, role modeling, and the provision of educational consequences are key strategies in cultivating integrity among children. Furthermore, the study highlights that anti-corruption education should not only be carried out through regulations but also through daily family practices supported by emotional bonding and communication. The contribution of this study lies in providing an empirical perspective on the significance of family-based character education as a foundation for anti-corruption culture. The research recommends that families, schools, and policymakers collaborate in reinforcing anti-corruption values through joint programs, curriculum integration, and public awareness campaigns. Therefore, nurturing integrity and anti-corruption behavior requires a collective effort beginning with the smallest unit of society: the family.